Butch/Femme differences in substance use and abuse among young lesbian and bisexual women: Examination and potential explanations. - Rosario, Margaret; Schrimshaw, Eric W; Hunter, Joyce (Substance use & misuse, 2008)
The current study examined the role of gender atypical self-presentation on the alcohol, tobacco, and marijuana use, as well as symptoms of substance abuse/misuse, of an ethnically diverse sample of 76 young (ages 14-21 years) lesbian and bisexual women who were interviewed between 1993 and 1995 in New York City. Even after controlling for age, sexual identity, and social desirability, young butch women reported drinking alcohol more frequently and in greater quantity, smoking more cigarettes, and using marijuana more frequently than young femme women. Experiences of gay-related stressful events, internalized homophobia, and emotional distress were found to largely account for the butch/femme differences in tobacco and marijuana use, but not in higher levels of alcohol use. Despite the small convenience sample, these findings suggest that intervention efforts to address the higher levels of substance use among young lesbian and bisexual women may increase effectiveness by also addressing experiences of gay-related stress and emotional distress of young butch women. The study's limitations are noted
Keywords: 1900-1999; 1990-1999; amériques; identités LGBTQIA2+; personnes bisexuelles; personnes lesbiennes; périodes historiques; ressource en ligne; régions géographiques; santé; thématiques; états-unis